Gestational diabetes affects fetal autophagy. (July 2017) - Avagliano, Laura; Massa, Valentina; Terraneo, Laura; Samaja, Michele; Doi, Patrizia; Bulfamante, Gaetano Pietro; Marconi, Anna Maria
Abstract: Autophagy is a catabolic process involved in the preservation of energy homeostasis and its dysregulation has been implicated in the development of metabolic disorders, including diabetes mellitus. Gestational diabetes mellitus represents a risk for fetal morbidity and mortality. The present study focuses on the autophagy process in human diabetic placenta and fetal pancreas, compared with controls. Analysis of the autophagy markers LC3, Beclin-1 and p62 suggests an impairment of the autophagy process in diabetic placentas. Results indicate an association between gestational diabetes and autophagy, emphasizing the importance of unravelling the mechanisms regulating this relationship. Highlights: Gestational diabetes increases autophagy markers expression in fetal pancreas. Autophagy process appears impaired in diabetic placentas. Placental autophagy is not related to glucose transporters expression.